Digital Comic Media to Improve Learning Outcomes in Understanding Narrative Texts for Grade IV Students - Lusiana, Mersita; Nuryanto, Sukarir (Journal of Education Reseach and Evaluation, 2025)
There are still many students who do not like reading activities. This is because monotonous activities have an impact on students who feel bored reading. This study aims to develop and test the effectiveness of digital comics in improving learning outcomes in understanding narrative texts for fourth-grade elementary school students. The research method used is research and development (R&D) with the Borg & Gall model. The subjects of the study consisted of 34 students, with small and large-scale trials. Data collection methods through observation, interviews, questionnaires, and tests in the form of pretests and posttests. The data collection instrument used a questionnaire sheet. The techniques used to analyze the data were qualitative descriptive analysis, quantitative analysis, and inferential statistics. The results of expert validation showed that this media was very feasible to use, with a score of 89.6% from material experts and 92.5% from media experts. Data analysis was carried out using the Shapiro-Wilk normality test, paired t-test to see the difference between pretest and posttest, and the N-Gain test, which showed an increase in student understanding in the high category with a score of 0.8271. It was concluded that digital comics have proven effective in improving student understanding through attractive visual presentation and a systematic storyline. Therefore, this media is recommended as an alternative for innovative technology-based learning to improve literacy and student learning outcomes in understanding narrative texts.